Agentes comunitários de saúde e o aleitamento materno: desafios relacionados ao conhecimento e à prática - Moimaz, Suzely Adas Saliba [UNESP]; Serrano, Mírian Navarro; Garbin, Cléa Adas Saliba [UNESP]; Vanzo, Ketlin Lara Tosta; Saliba, Orlando [UNESP] (ABRAMO Associação Brasileira de Motricidade Orofacial, 2017)
ABSTRACTPurpose: to identify the knowledge of community health workers on practices and promotion of breastfeeding.Methods: this is a cross-sectional descriptive study aimed to investigate a sample of 148 health workers quantitatively and qualitatively. Data collection was performed by applying a semi-structured questionnaire with open and closed questions. The following variables were analysed: sociodemographic data, capacity to provide breastfeeding guidance, participation in training and courses, and knowledge of the breastfeeding benefits for mother and baby. Statistical analysis was performed with chi-square test, exact Fisher’s test and G-test at significance level of 5%. Open questions were analysed according to the qualitative research technique.Results: approximately, 45.95% of the health workers were not trained to provide nursing mothers with practical guidance on breastfeeding, and 63.30% never attended courses on breastfeeding. The majority of health workers mentioned breastfeeding benefits only for the baby, namely: nutrition, immunology, development, health, dentition, and bones. There was a statistically significant association between the capacity to provide breastfeeding guidance and participation in training (p<0.001).Conclusion: the health workers had not participated in training courses to follow up nursing mothers, in addition to having a limited knowledge on practices and promotion of breastfeeding and paying late post-natal home visits.

RESUMOObjetivo: identificar o conhecimento de Agentes Comunitários de Saúde sobre as práticas e a promoção do aleitamento materno.Métodos: estudo transversal, descritivo, inquérito, quanti-qualitativo realizado com amostra de 148 agentes. A coleta de dados foi realizada por meio da aplicação de um questionário semiestruturado, com questões abertas e fechadas. Foram analisadas as variáveis: sociodemográficas, capacidade para orientação sobre o aleitamento, participação em treinamentos/cursos, conhecimentos sobre vantagens do aleitamento para mãe e bebê. Realizou-se análise estatística descritiva, foram empregados os testes Qui-quadrado, Exato de Fisher e G, ao nível de significância 5%. As questões abertas foram analisadas segundo a técnica de pesquisa qualitativa.Resultados: aproximadamente, 45,95% dos agentes não foram capacitados para realizar orientação prática das nutrizes sobre o aleitamento e 63,30% nunca participaram de cursos sobre amamentação. A maioria citou vantagens do aleitamento relacionadas, somente, ao bebê, emergindo as categorias: nutrição do bebê, imunológica, desenvolvimento/saúde do bebê, dentição/ossos. Houve associação estatisticamente significante entre capacidade de orientar as mães na amamentação e participação em treinamentos (p<0,001).Conclusão: os agentes não haviam participado de cursos de capacitação para acompanhar as nutrizes, apresentaram conhecimento limitado sobre a prática e a promoção do aleitamento, e as visitas domiciliares realizadas pós-parto ocorreram tardiamente.
Community health workers and breastfeeding: challenges related to knowledge and practice
Keywords: Community Health Works; Breastfeeding; Knowledge; Agentes Comunitários de Saúde; Aleitamento Materno; Conhecimento